The tax treatment of losses arising in loans advanced - Cochrane, Graham David (Department of Commercial Law, 2021)
Our law recognises two types of loans, namely a loan for use (commodatum) and a loan for consumption (mutuum)'. In a loan for use something is delivered for use by a borrower without reward, and the borrower is obliged to return the same thing he received on loan. For example, a person may lend another person an asset of his, and when the recipient has finished using that asset the identical asset in the same condition as received, is to be returned to the lender. In a loan for consumption one or more units of some fungible thing are delivered to the borrower. The borrower may consume what has been received but is bound to return the same number of units of the type of the thing borrowed. In constrasting a commodatum with a mutuum, it can be seen that a lender ·in the first instance retains ownership of the asset loaned, whereas in the second, ownership is passed to the borrower, who undertakes to repay the loan by delivering things of an identical quality and quantity as those borrowed. Thus, an essential characteristic of a loan of money is that the lender is either the owner of the funds advanced, or is authorised to make the loan by the owner. Once delivery has taken place to the borrower a contract can probably be said to be binding. 2 Thus, a contract of loan cannot be said to be binding by part performance as, in mutuum the only person bound is the person who received a service by the handing over of the money in question.